THE CONSTRUCTION OF MEANING IN THE TEXT “THERE’S NO PEACE IN BOARD OF PEACE. FREE PALESTINE” IN THE STAGE VISUALS OF FEAST’S CONCERT: A PRAGMASEMANTIC STUDY - Aisyah Sahla Saudah; Nafsiyah Puspa Pratiwi; Siti Humairoh; Tatu Siti Rohbiah (IdeBahasa, 2026)
Language in visual media does not merely function as a decorative element, but also as a semiotic unit that actively constructs and conveys meaning. This study examines the construction of meaning in the text "There's No Peace in Board of Peace. Free Palestine" displayed in the stage visuals of Feast's concert through a pragmasemantic approach. This text emerges from two contemporary issues that are linguistically relevant, namely the ongoing Israeli aggression against Gaza and Indonesia's decision to join the Board of Peace in January 2026, rendering these issues urgent objects of pragmasemantic inquiry. This study employs a descriptive qualitative method with an inductive approach, in which theory does not precede data but emerges from the analytical process itself. Data were collected through a documentation technique, namely a screenshot of a post on the Instagram account @ffeastt uploaded on February 12, 2026. Analysis was conducted through three stages of data analysis technique, namely data reduction, data display, and drawing and verifying conclusions, with the integration of semantic and pragmatic dimensions as the analytical core. The findings were presented in a pragmasemantic analysis table and a descriptive narrative. The findings reveal interrelated lexical, grammatical, denotative, and connotative meanings across all three units. Semantically, the three phrases construct a layered socio-political message. Pragmatically, they perform different speech-act functions whose implicatures converge on one message: genuine peace cannot exist without Palestinian independence. The construction of meaning follows a coherent argumentative logic of condition, irony, and solution.